Bureaucracy Reform In The Body of The Indonesian National Police (Applying The Principle of Professionality - Septia Saputri, Adhalia (Devotion : Journal of Research and Community Service, 2022)
State administrators have a very important role in realizing a clean and free country from corruption, collusion, and nepotism. State administrators must work hard and cooperate with the community. This is in accordance with the ideals of the nation's struggle to create a just and prosperous society as stated in the 1945 Constitution of the Republic of Indonesia. principles of state administration. State administrators in this case the National Police as a state instrument that has a role in maintaining public security and order, enforcing the law, and providing protection, protection, service, and a good example to the community. Demands for the professionalism of the Police are now being intensively voiced by the public. This community demand is to reform the police bureaucracy.